Information Needs and Information-Seeking Behaviour of Students of Federal College of Dental Technology and Therapy (FCDT&T), Enugu, Nigeria - Oguonu, Oluchukwu Clara (POMLIF Journal of Library and Information Science, 2021)
The study examines the information needs and information-seeking behavior among the students of the Federal College of Dental Technology and Therapy, Enugu, Nigeria. A total sample population of Two Hundred (200) respondents was selected from the four existing departments in the 2017/2018 academic session. The questionnaire was used as the research instrument for data collection. Simple percentages, tables and frequencies were used for data analysis and present action for easy interpretation. The findings indicate that the main information needs of students pertain to tasks involving academic research (190:97.44%) and information on tests and examinations (185:94.89%). Consultation with lecturers and colleagues in the field (191:97.95%) and browsing through the internet (189:96.92%) and electronic database (187:95.90%) are the most consulted and preferred source of information. Meanwhile, doing assignments, classwork, project research and preparing for examination (191:97.95%) are the main purposes of seeking information. The main barriers to information-seeking by students are the lack of reading and inadequate information materials (191:97.95%) which negatively correlates to the perception of success in meeting their information needs. Hence, the study recommends the adequate provision of resources and the organizing of library user education at the beginning of every semester for all students to enhance their information seeking, and usage technology-driven era.